2022
DOI: 10.1016/j.jhin.2021.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel plasmid in Serratia marcescens harbouring blaGES-5 isolated from a nosocomial outbreak in Japan

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The incidence of carbapenemase-producing infections significantly increases mortality and medical costs ( Gasink et al, 2009 ; Otter et al, 2017 ). GES-type carbapenemase producers are present in hospitals for prolonged time, causing outbreaks within hospitals ( Boyd et al, 2015 ; Yamasaki et al, 2017 ; Ellington et al, 2020 ; Literacka et al, 2020 ; Nakanishi et al, 2022 ; Yoo et al, 2023 ). However, the genetic features of resistant isolates are not well understood, and their diffusion capabilities could be underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of carbapenemase-producing infections significantly increases mortality and medical costs ( Gasink et al, 2009 ; Otter et al, 2017 ). GES-type carbapenemase producers are present in hospitals for prolonged time, causing outbreaks within hospitals ( Boyd et al, 2015 ; Yamasaki et al, 2017 ; Ellington et al, 2020 ; Literacka et al, 2020 ; Nakanishi et al, 2022 ; Yoo et al, 2023 ). However, the genetic features of resistant isolates are not well understood, and their diffusion capabilities could be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of carbapenemase producers threatens the effective treatment of gram-negative bacterial infections, owing to their resistance to the most β-lactams, which are commonly used antibiotics, thus limiting therapeutic options ( Gasink et al, 2009 ; Otter et al, 2017 ; Bonomo et al, 2018 ). Guiana extended-spectrum (GES)-type carbapenemase producers are prevalent in both clinical and environmental settings and are known to cause nosocomial outbreaks ( Boyd et al, 2015 ; Naas et al, 2016 ; Yamasaki et al, 2017 ; Ellington et al, 2020 ; Literacka et al, 2020 ; Nakanishi et al, 2022 ; Yoo et al, 2023 ). The bla GES genes are essentially linked to mobile genetic elements, which promote the spread of resistance genes to clinically relevant pathogenic bacteria and have been observed within integron gene cassettes on plasmids with diverse types of replicons ( Naas et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…GES carbapenemases are relatively rare among clinical isolates, whereas they are increasingly detected in aquatic environments ( 16 ). Nonetheless, outbreaks of GES-5-producing Pseudomonas aeruginosa and Serratia marcescens have been reported in Japan ( 17 , 18 ). In a very recent study, we found that bla GES-24 and bla GES-5 , which are mainly carried by Klebsiella and Enterobacter spp., are the only carbapenemase genes detected in wastewater effluent from a hospital with no history of detection of clinical GES carbapenemase-producing isolates ( 19 ).…”
Section: Introductionmentioning
confidence: 99%